Depositional and post-depositional setting of Maastrichtian limestone, Ariyalur Group, Cauvery Basin, South India:a geochemical appraisal - Nagendra R.; Ramasamy, Nagarajan; Bakkiaraj D.; Armstrong-Altrin J. (Springer, 2011)
Major, trace, REE, and stable isotopic composition of Maastrichtian limestones of Cauvery Basin were studied to decipher their depositional and post-depositional environment. The major oxides and trace elements concentration of these limestones were normalized using Post-Archean Australian Shale (PAAS) values. The concentration of CaO is having a significant enrichment, and MgO, K2O, Co, Ni, Cu, Zn, Pb, Ba, U, and Th are moderately depleted, whereas Sr and Na2O contents are relatively similar to the PAAS values. The PAAS-normalized REE + Y pattern of Maastrichtian limestones display relatively uniform pattern among the compositionally different limestones: (1) enriched LREE (average NdSN/YbSN = 5.03 ± 0.92); (2) positive Ce anomaly (average 1.79 ± 0.16); (3) negative GdSN/Gd* anomaly (average 0.52 ± 0.02); (4) low Y/Ho ratio (average Y/Ho = 0.14 ± 0.01). The average ΣREE contents in ferruginous, arenaceous, and biostromal limestones are 65, 64, and 52 ppm, respectively, which indicate that the mineralogical variation plays a major role in incorporation of ΣREE. The Kallankurichchi limestones have δ13C values range from −3.2 to −1.1‰PDB, and the δ18O values range between −7.8 and −5.5‰PDB. The negative δ13C and δ18O values and a moderate co-variation between δ13C and δ18O (r 2 = 0.35) indicate that the alteration of original isotopic composition is due to diagenesis.The positive Ce/Ce* confirms the clastic input into the system, and negative Mn* values and Th/U ratios (~0.29–1.4) in these limestones indicate their association with precipitation of carbonates in reducing (anoxic–dysoxic: Th/U ≤ 2) conditions.